Protein Expression Profile and Transcriptome Characterization of Penicillium expansum Induced by Meyerozyma guilliermondii - Qiya Yang; Dhanasekaran Solairaj; Maurice Tibiru Apaliya; Mandour Abdelhai; Marui Zhu; Yuan Yan; Hongyin Zhang (Journal of Food Quality)
Antagonistic yeasts can inhibit fungal growth. In our previous research, Meyerozyma guilliermondii, one of the antagonistic yeasts, exhibited antagonistic activity against Penicillium expansum. However, the mechanisms, especially the molecular mechanisms of inhibiting activity of M. guilliermondii, are not clear. In this study, the protein expression profile and transcriptome characterization of P. expansum induced by M. guilliermondii were investigated. In P. expansum induced by M. guilliermondii, 66 proteins were identified as differentially expressed, among them six proteins were upregulated and 60 proteins were downregulated, which were associated with oxidative phosphorylation, ATP synthesis, basal metabolism, and response regulation. Simultaneously, a transcriptomic approach based on RNA-Seq was applied to annotate the genome of P. expansum and then studied the changes of gene expression in P. expansum treated with M. guilliermondii. The results showed that differentially expressed genes such as HEAT, Phosphoesterase, Polyketide synthase, ATPase, and Ras-association were significantly downregulated, in contrast to Cytochromes P450, Phosphatidate cytidylyltransferase, and Glutathione S-transferase, which were significantly upregulated. Interestingly, the downregulated differentially expressed proteins and genes have a corresponding relationship; these results revealed that these proteins and genes were important in the growth of P. expansum treated with M. guilliermondii.